Corporate Personality Theory and Changes in Accounting Methods: An Empirical Test. - Shank, John K.; Copeland, Ronald M. (The Accounting Review, 1973)
This article presents information on an empirical study designed to provide additional evidence about changes in accounting methods. The primary responsibility for effecting accounting changes currently rests with the management of a reporting firm. This results from a structure of accounting authority which leans heavily upon "general acceptance" of accounting practices among statement issuers and which allows flexibility for managers to tell their story as they see it. As long as this framework prevails, the primary pressure point for effecting changes in reporting practices will continue to be the management of the reporting firm. One can define an innovation as an idea perceived as new by the individual even if, in fact, it is not new. Diffusion is the process by which adoption of the innovation spreads. In terms of primary emphasis, this view differs substantially from that reflected in the diffusion of innovation studies which suggest that accounting change behavior is related primarily to the characteristics of the innovative accounting methods themselves, rather than to the behavioral set of the changer. Accounting change behavior is a complex phenomenon which is probably influenced to some extent both by the behavioral set of potential changers and by the characteristics of the particular changes as well as by other factors.